Association between the incidence and mortality rates for corpus uteri cancer and human development index (HDI): a global ecological study - Zaher Khazaei; Elham Goodarzi; Malihe Sohrabivafa; Hasan Naemi; Kamyar Mansori (Korean Society of Obstetrics and Gynecology, 2020)
ObjectiveThe aim of this study was to determine the association between the incidence of and mortality due to corpus uteri cancer (CUC) and the human development index (HDI) across the world.MethodsThis was an ecological study. The incidence and mortality rates of CUC along with HDI data were extracted from the Global Cancer Data in 2018. Subsequently, correlation coefficient and linear regression model were used to determine the association between the incidence and mortality rates of CUC and the HDI. STATA-14 was used for data analysis.ResultsThere was a positive and significant correlation between the incidence (r=0.693; P<0.001) and mortality (r=0.284; P<0.001) rates of uterine cancer and the HDI. A positive and significant correlation was also observed between the incidence rate and the gross national income per 1,000 capita (r=0.440; P<0.001), mean years of schooling (MYS) (r=0.740; P<0.001), life expectancy at birth (LEB) (r=0.590; P<0.001), and expected years of schooling (r=0.650; P<0.001). The results of the linear regression model showed a significant statistical association between MYS and the incidence of CUC (β=1.10; 95% confidence interval [CI], 0.60-1.70) and LEB and mortality due to uteri cancer (β=0.40; 95% CI, 0.10-0.90).ConclusionThe results of this study suggest a significant statistical association between the incidence and mortality rates of CUC and the HDI.